The Future of Counselling Psychology Education and Training in Canada: A Post-Conference Reflection - Wada, Kaori; Kassan, Anusha; Domene, José F.; Bedi, Robinder; Kintzel, Franziska; West, Alyssa (Canadian Journal of Counselling and Psychotherapy, 2020)
This article summarizes and elaborates upon the themes discussed by members of the “Future of Counselling Psychology Education and Training in Canada” working group at the 2018 Canadian Counselling Psychology Conference (2018 CCPC) by 19 participants in attendance. Complexities in program requirements, external and internal program regulations, research competency and advancement, and cultural/social justice responsiveness and internationalization are explicated and analyzed. The current state of counselling psychology education and training is highly intricate and nuanced, while many strengths and opportunities for growth exist despite some long-standing tensions. It is hoped that this article not only will help outline and contextualize the current status and challenges facing the future of counselling psychology education and training in Canada but also will recruit others in helping to improve Canadian counselling psychology education and training. Advocating for what is needed to achieve this is consistent with the theme of the 2018 CCPC. Continued dialogue, program evaluation, theorizing, and research are needed on the nature and dynamics of Canadian counselling psychology education and training.